Redefining Success - Ricci, Carlo (Paideusis)

(untitled) (Canadian Philosophy of Education Society, 2007)
Two interconnected arguments are made: 1) that we eliminate standardized testing 2) that we oppose mainstream schooling. Schooling and education are two very different concepts, and do not necessarily coincide in practice. A case in point: our current schooling system is anti-educational. This paper makes the case for unschooling and learner-centred democratic alternatives.